Autonomies in Interaction: Dimensions of Patient Autonomy and Non-adherence to Treatment - Arrieta Valero, Ion (Frontiers in Psychology, 2019)
In recent years, several studies have advocated the need to expand the concept of patient autonomy beyond the capacity to deliberate and make decisions regarding a specific medical intervention or treatment (decision-making or decisional autonomy). Arguing along the same lines, this paper proposes a multidimensional concept of patient autonomy (decisional, executive, functional, informative and narrative) and argues that determining the specific aspect of autonomy affected is the first step towards protecting or promoting (and respecting) patient autonomy. These different manifestations of autonomy are not mutually dependent; there may be patients who have problems in one dimension, while at the same time being fully autonomous in others. Nevertheless, a close interaction has been observed between the various dimensions and indeed, a phenomenological analysis shows that damage to or a reduction in one aspect of people’s capacity for self-government generally affects other aspects of their autonomy, which in turn disrupts their identity and the way in which they see themselves and are seen by others. In this paper, I shall examine some of these interactions and show how they may lie at the heart of the problem of poor treatment adherence (where adherence is defined as being the extent to which a patient’s behavior over time coincides with the recommendations made by and agreed with their health professional). One example given is that of psoriasis, a chronic skin disease with a very poor adherence record. In Spain, it is calculated that 85% of patients diagnosed with mild to moderate psoriasis fail to comply properly with their treatment, and figures from other parts of the world are similar. Although there are many possible causes for non-adherence among psoriasis patients, assessing their decisional, executive and narrative capacities and taking appropriate action based on the results may help increase adherence rates.